KARAKTERISTIK PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Sugeng Santoso PN (MIMBAR YUSTITIA, 2018)
There are two mechanisms for resolving the industrial relations disputes, namely through litigation and non-litigation practices. The litigation practice is performed by filing an industrial relations dispute to the industrial relations court. The non-litigation practce offers three institutions, such as through conciliation, mediation and arbitration. The dispute settlement of industrial relations turned out to have characteristics that differs it from other dispute settlement. The characteristics of the dispute settlement of industrial relations occur because of the principles of resolving industrial relations disputes. The principles of industrial relations dispute resolution are universally applicable and some arise based on the industrial relations system that applies in each country. This paper discusses about legal issue : Principles of resolving industrial relations disputes.